HUKUMAN PEZINA DI DESA LUBUK RUSO BATANG HARI JAMBI: Perjumpaan Adat Dan Hukum Islam - Dody Sulistio (Lembaga Penerbitan Jurnal Ilmiah Institut Agama Islam Bani Fattah Jombang, 2023)
Abstract: This paper aims to find out the sanctions for adultery perpetrators in the “adat” law of Batang Hari, Jambi Province, to be precise in Lubuk Ruso Village. Adultery according to local custom is an act that cannot be justified, therefore custom regulates sanctions against anyone who commits adultery in the village of Lubuk Ruso. The sanction is in the form of a fine of one goat and 100 rice paid in cash. In addition to this, adulterers are also given social sanctions in the form of exile from their hometown for one year, the aim is to prevent the village from disaster due to adultery. The implementation of customary law sanctions against perpetrators of adultery, although not exactly the same as the provisions contained in the ghoiru muhson adultery sanctions in Islamic law, cannot be separated from the influence of Islamic values in practice as in the traditional slogan